Radiofrequency Ablation in Brugada Syndrome - Almiz, Pavlo O.; Topchii, Alina V. (Ukrainian Journal of Cardiovascular Surgery, 2022)
In 1992, Brugada brothers first described the clinical-electrocardiographic syndrome which was characterized by changes in the electrocardiogram (ECG), family history of syncopal states and sudden cardiac death (SCD) in the absence of structural heart disease. The standard therapy recommended by the European Society of Cardiology for the prevention of SCD in type I Brugada syndrome (BS) is implantation of a cardioverter-defibrillator. Radiofrequency ablation (RFA) of BS has been performed since the 2000s as an alternative therapy for BS with recurrent ventricular arrhythmias. To date, more than 300 such interventions have been performed by various centers around the world, and multicenter randomized trials are underway to study the long-term results of catheter destruction. We reviewed our experience of catheter ablation in a patient with BS. The patient suffered from ventricular arrhythmias and short-term loss of consciousness. ECG and 24-hour monitoring data recorded ventricular arrhythmias of more than 34% per day and type II BS. Electroanatomical mapping and RFA of the areas with low amplitude graphics were performed by endocardial access. This zone coincided with the earliest activation of the myocardium during ventricular arrhythmias. Extrasystoles were eliminated. In the remote period (10-12 weeks) the patient had no ventricular arrhythmias and there are also no ECG signs of BS. Most major arrhythmological centers perform RFA with epicardial access. Our patient chose the endocardial approach as safer. In her specific case, localization of arimogenic substrate allowed to limit this access, and RFA was successful.